Pressure−impulse diagram method – a fundamental review. Issue 2 (6th June 2019) - Chernin, Leon; Vilnay, Margi; Shufrin, Igor; Cotsovos, Demetrios
Abstract : Accidental and deliberate explosions stemming from catastrophic events in the petroleum industry, incidents during complex manufacturing processes, mishandling or failure of domestic gas appliances or installations, terrorist attacks and military engagements, are becoming increasingly relevant in structural design. Pressure−impulse ( P – I ) diagrams are widely used for the preliminary assessment and design of structures subjected to such extreme loading conditions. A typical P – I diagram provides information concerning the level of damage sustained by a specific structural member when subjected to a blast load. This paper presents a state-of-the-art review describing the development of the P – I diagram method over the past 70 years, the main assumptions on which its development is based and the framework through which such a method is applied in practice. The structural analysis methods used for the derivation of P – I curves are discussed and the existing approaches are categorised according to algorithms used. A review of the P – I curve formulae proposed to date is performed, where the formulae are classified according to the formulation methods.